Studies on the mechanisms of lead neurotoxicity and oxidative stress in human neuroblastoma cells - Naarala, Jonne (1997)
Excitotoxicity and oxidative stress are two phenomena that have repeatedly been described as being involved in a wide range of disorders of the nervous system including epilepsy, ransient cerebral ischemia, Alzheimer's disease, Parkinson's disease and Huntington's disease. Glutamate, aspartate, and acetylcholine are the major excitatory neurotransmitters in the brain. The coexistence and co-release of neurotransmitters and their association in neuronal events, and coupling mechanisms have recently evoked considerable interest in the way these are related to excitatory neuronal damage and death. In the present study, oxidative stress evoked by glutaminergic and muscarinic receptors, and its modulation by an environmental toxin, lead, was studied in a human neuroblastoma cell line. The results of the present study show that human SH-SY5Y neuroblastoma cells express glutamate receptor subtypes. Activation of these receptors elicits functional intracellular calcium responses. Their stimulation by glutamate increases the production of reactive oxygen species although this is seen only after the impairment of the cellular glutathione defense system. Glutamate together with lead causes sustained production of reactive oxygen intermediates and subsequent oxidative stress. Protein kinase C may have an important role in the onset of oxidative stress because the production of reactive oxygen species by glutamate is completely inhibited by a protein kinase C inhibitor. Moreover, protein kinase C inhibition together with lead treatment causes oxidative stress. This may be due to modulation of the phosphorylation status of protein kinase C target proteins. The stimulation of cholinergic muscarinic receptors seems to increase the production of reactive oxygen intermediates in this cell line; cholinergic-induced oxidative stress seems to be protein kinase C-controlled and to be due to increased production of the superoxide anion. The principal route for phorbol ester-induced differentiation of SH-SY5Y cells may be down-regulation of protein kinase C. Also the differentiation of these cells promoted by lead seems to be under the partial control of protein kinase C. The present findings shed new light on the role of the glutaminergic and cholinergic neurotransmitter systems in oxidative stress. Also, the SH-SY5Y cell line proved to be an effective tool in investigating the effects of stimulation of different receptor systems and their modulation by lead. This study proposes a new mechanism for lead neurotoxicity through amplification of glutamate-mediated cellular activation.